Word : a cross-linguistic typology - Dixon, Robert M. W.; Aĭkhenvalʹd, A. I͡U. (Aleksandra I͡Urʹevna) (Cambridge University Press, 2002)
In this book, a distinguished international group of scholars discuss the concept 'word' and its applicability in a range of typologically diverse languages from all corners of the globe. Close study of their phonological and grammatical characteristics enables us to refine our understanding of what can constitute a 'word'.